Paraneoplastic pemphigus: a clinical, laboratorial, and therapeutic overview - Maruta, Celina Wakisaka (An Bras Dermatol, 2019)
Paraneoplastic pemphigus is a rare and severe autoimmune blistering disease characterized by mucocutaneous lesions associated with benign and malignant neoplasms. Diagnostic criteria include the presence of chronic mucositis and polymorphic cutaneous lesions with occult or confirmed neoplasia; histopathological analysis exhibiting intraepidermal acantholysis, necrotic keratinocytes, and vacuolar interface dermatitis; direct immunofluorescence with intercellular deposits (IgG and C3) and at the basement membrane zone (IgG); indirect immunofluorescence with intercellular deposition of IgG (substrates: monkey esophagus and simple, columnar, and transitional epithelium); and, autoreactivity to desmogleins 1 and 3, desmocollins 1, 2, and 3, desmoplakins I and II, envoplakin, periplakin, epiplakin, plectin, BP230, and α-2-macroglobulin-like protein 1. Neoplasias frequently related to paraneoplastic pemphigus include chronic lymphocytic leukemia, non-Hodgkin lymphoma, carcinomas, Castleman disease, thymoma, and others. Currently, there is no standardized treatment for paraneoplastic pemphigus. Systemic corticosteroids, azathioprine, mycophenolate mofetil, cyclosporine, rituximab, cyclophosphamide, plasmapheresis, and intravenous immunoglobulin have been used, with variable outcomes. Reported survival rates in 1, 2, and 5 years are 49%, 41%, and 38%, respectively.